The Role of Job Crafting in mediating the effect of servant leadership and employee engagement: An Empirical Study of the Service Sector in Malaysia - Chuah, Soo-Cheng; Abdul Rahim, Abdul Rahman; Cheam, Chai Li; Zulkefle, Nur Maisarah (Advances in Social Sciences Research Journal, 2023)
In Malaysia, there has been relatively little empirical study on servant leadership, particularly in relation to job engagement and job crafting. Research has found that leadership has a significant impact on employee engagement, which in turn influences organizational performance. In order to better understand how servant leadership affects employee engagement, this study looks at how job crafting, as mediating factor, influences the former two variables in the Malaysian service industry. An online survey was used in this study to purposively sample 154 employees of the service industry in the Klang Valley, Malaysia. Servant Leadership Measures (SL-7), Work Crafting Questionnaire (JCQ), and Utrecht Work Engagement Scale (UWES-9) are the respective instruments utilized in this study to assess servant leadership, job crafting, and employee engagement. The data was analyzed using the partial least squares structural equation modeling (PLS-SEM) method, and the findings demonstrated that servant leadership and job crafting significantly increase employee engagement in the service industry. A partial mediation analysis of the link between servant leadership and employee engagement showed that job crafting mediates this association positively. The results indicate that servant leadership is a successful leadership style that raises employee job engagement and nurtures their enthusiasm for work through job crafting. The study’s findings are significant in that they give practitioners and organizations insight into the need for the servant leadership idea in various circumstances. This is due to its capacity to promote organizational and employee growth. In addition to fostering great team dynamics, servant leadership has the power to completely reshape cultures and organization.